IMPLEMENTASI METODE PEMBELAJARAN VIRTUAL LABORATORY (PRAKTIKUM ROBOTIKA) DENGAN CIRCUIT WIZARD SAAT PANDEMI COVID-19 - Muhammad Lukman Hadi (Approach : Jurnal Teknologi Penerbangan, 2019)
In this article, we will discuss how to learn practicum during the Covid-19 pandemic. The Line Follower robot practicum with the circuit wizard application uses the blanded learning method so that students are able to create and innovate online with offline combinations. This robot is a type of automation equipment that can follow the movement of the path through sensors that will be made in electronic devices.We know that during this pandemic, especially in Vocational School practicum learning for face-to-face is very limited. With this solution, it is hoped that they will be able to train and collaborate between teachers and students while still prioritizing health protocols.In the Line Follower series, there are 3 main parts, namely the sensor, comparator and driver. For the sensor part, a photodiode is used as a light sensor, while the comparator uses IC LM 324 as a voltage comparison and for the driver, 2 motors are used to drive the wheels.The test results of the Line Follower series show that they are capable of running on several fields, including straight, turning, rising, and descending fields.